3D reconstruction of UAV remote sensing sequence image based on iterative constraint weighting. (12th October 2021) - Sun, Tiebo; Li, Meng; Wang, Weibing; Liu, Chunyue
Aiming at the problem that the traditional 3D reconstruction method of UAV remote sensing sequence images takes time and affects the reconstruction accuracy, a 3D reconstruction method of UAV remote sensing sequence images based on iterative constraint weighting is proposed. Construct a UAV remote sensing platform, and process the images of UAV remote sensing sequences through image enhancement, uniform light processing and stitching. An iterative constraint weighting method is introduced to solve the global rotation matrix problem as a rotation vector in algebra. Through the iterative constraint weighting method, the second programming obtains the optimal solution of the global position and optimises the global position and attitude. According to the position and attitude parameters of the acquired UAV remote sensing sequence image and the reconstruction point cloud, the 3D reconstruction of the image is realised. Experimental results show that the method is short, accurate, effective and reliable.